An impact of the novel coronavirus infection (COVID-19) on human reproductive function - E. V. Garibidi; E. P. Shatunova; T. A. Fedorina; D. E. Garibidi (Акушерство, гинекология и репродукция)
The latest data on the impact of the novel coronavirus infection (COVID-19) on female and male reproductive health are reviewed. Pathological changes in organs and tissues of human reproduction system after COVID-19 as well as  recommendations for rehabilitation of couples planning pregnancy after COVID-19 are discussed. Moreover, issues of the reproductive health resulting from altered psychologic status in women after COVID-19 were highlighted as well.